Cultivo de anteras y mejoramiento de plantas - Roca, W.; Nunez, VM; Mornan, K (International Center for Tropical Agriculture, 1991)
Different aspects of anther culture are reviewed as follows: its application in plant breeding, conditions that affect results (physiology and genotype of donor plants, albinism, pollen development, pretreatment of anthers, culture media), var. obtained by anther culture, and comparative advantages of this technique in plant breeding work. In cassava, research at CIAT seeks to develop methods to produce haploids/diploids, allowing homozigosity to be reached quickly. Approaches used for work in cassava are androgenesis, gynogenesis, and interspecific and intergeneric crosses. (CIAT)